Horn - A sustainable material for the future - Ridderström,Tone (Diploma work, 2022)
Cow horn has been a craftig material in Europe for 1000s of years. Yet, in the last 100 years the material has disappeard from our pool of commonly used materials. Today it is mostly used for dogfood and gelatine. I believe that horn could again become a commonly used crafting material, especially for modern and sustainable products. Among my many visions for horn, I see it as a beautiful, natural material that could be used instead of plastic. In this project im setting out to explore the propertis, advantages and disadvantages of cow horn and how to use it for contemporary products in modern production.